1986
DOI: 10.1152/ajpheart.1986.250.2.h151
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular regional work from wall tension-area loop in canine heart

Abstract: To quantitatively evaluate left ventricular (LV) regional work, LV pressure-volume relation and wall tension-regional area (TA) relation were analyzed in the excised cross-circulated left ventricle connected to a volume servo pump system. Wall tension was calculated using Laplace's law for a spherical model, and regional area was determined from orthogonal segment lengths measured with pairs of ultrasonic crystals. Data were obtained by changing LV end-diastolic volume or stroke volume before and after dobutam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Our use of short-axis diameter as the diameter of the sphere might 476 result in a small underestimation of regional work. 16 In addition, in a regionally ischemic heart, changes in regional radius of curvature, which were not measured in the present study, would occur in the ischemic region, and hence might affect wall tension of this region . 31 However, our previous study22 has shown that the global integral of regional work determined by the T-A loop method closely agrees with measured total left ventricular work both before and after coronary occlusion, suggesting that the influence of changes in regional wall tension on the measurement of regional work during regional ischemia is very small.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Our use of short-axis diameter as the diameter of the sphere might 476 result in a small underestimation of regional work. 16 In addition, in a regionally ischemic heart, changes in regional radius of curvature, which were not measured in the present study, would occur in the ischemic region, and hence might affect wall tension of this region . 31 However, our previous study22 has shown that the global integral of regional work determined by the T-A loop method closely agrees with measured total left ventricular work both before and after coronary occlusion, suggesting that the influence of changes in regional wall tension on the measurement of regional work during regional ischemia is very small.…”
Section: Discussionmentioning
confidence: 58%
“…First, the pressure-length loop method can provide only unidirectional assessment of regional function, whereas myocardial fibers are variously oriented within the left ventricle30 and the extent and time course of segment shortening are different depending on the orientation of the segment. 16,[24][25][26] Second, the dimensions of the pressure-length loop area (mm Hg.cm or dyne/cm) differ from those of work or energy (dyne cm or joule). 16' 21 In contrast, the T-A loop area (mm Hg.ml) has the same dimensions as work or energy because 1 mm Hg.ml = 1.33 x 10 J.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The area enclosed by the left ventricular stress-strain loop during a single heartbeat was calculated as the EW of the myocardial region (in J/m 3 ), normalized per unit of volume (10,19,28). Stress-strain area (SSA, in J/m 3 ), the regional equivalent of the pressure-volume area (PVA), an index of total ventricular work, was calculated as the area enclosed by the end-systolic and end-diastolic relations and the systolic trajectory of the stress-strain loop (14,24).…”
Section: Generalmentioning
confidence: 99%
“…Similarly, mean regional strain (⑀) was derived from the geometric mean according to (10) The technical assistance of Jan R. van Meegen and Rob H. van Bremen is gratefully acknowledged. …”
Section: Appendixmentioning
confidence: 99%